Health-related quality of life among elderly individuals with chronic obstructive pulmonary disease - طنوس, سائر (Latakia University Journal -Medical Sciences Series, 2024)
Chronic obstructive pulmonary disease (COPD) is a common condition that affects the health of older adults. Elderly individuals with COPD experience symptoms such as shortness of breath, increased mucus production, and persistent coughing, which negatively impact their quality of life. Therefore, comprehensive support should be provided to improve the quality of life and general well-being of these patients. The aim of this study was to assess the health-related quality of life among elderly individuals with COPD. The study included a convenience sample of 100 male and female patients, and data were collected at Tishreen University Hospital in Latakia. The results revealed that the majority of patients had poor quality of life in terms of disease-related symptoms, with more than two-thirds of the sample experiencing a poor quality of life due to the impact of the disease. The study recommended the implementation of specialized rehabilitation and training programs for elderly individuals with COPD, including respiratory exercises, self-care techniques for symptom management, and patient education on preventing symptom exacerbation. Key words: Quality life, Chronic obstructive pulmonary disease (COPD).